ATP increases the migration of microglia across the brain endothelial cell monolayer. Issue 2 (15th April 2016) - Maeda, Tomoji; Inagaki, Manato; Fujita, Yu; Kimoto, Takehiro; Tanabe-Fujimura, Chiaki; Zou, Kun; Liu, Junjun; Liu, Shuyu; Komano, Hiroto
Abstract : To elucidate the mechanism of microglial migration across the blood–brain barrier (BBB), we developed an in vitro co-culture system and analysed real-time BBB integrity during transmigration. We show that ATP promotes microglia transmigration via a mechanism involving microglial matrix metalloproteinases (MMPs). Abstract : The cerebral microcapillary endothelium, known as the blood–brain barrier (BBB), acts as a barrier between the blood and the interstitial fluid of the brain. The BBB therefore controls the passage of nutrients into the central nervous system (CNS). Microglia show a specific affinity for migration into the CNS, and this migration appears to occur independently of BBB integrity. To study the migration of microglia across the BBB, we developed an in vitro co-culture system of mouse brain endothelial cells (MBECs) and Ra2 microglia using Transwell inserts. We first investigated the influence of microglia or ATP, a microglial chemotactic factor, on MBEC barrier integrity. The addition of microglia or ATP led to the disruption of the MBEC monolayer and significantly decreased barrier function as measured by trans-endothelial electrical resistance (TEER) and electric cell–substrate impedance sensing (ECIS). Furthermore, ATP promoted the migration of microglia but not macrophages across the MBEC monolayer. An inhibitor of matrix metalloproteinases (MMPs) decreased the transmigration of microglia in our system, indicating that MMPs play a role in microglial chemotaxis. We specifically identify a role for microglia-derived MMP-2. In conclusion, we offer evidence that microglia migration across the brain endothelial cell monolayer is increased in the presence of ATP in a manner that involves MMP secretion.